Religion, Revolution, and Regional Culture in Eighteenth-Century France : The Ecclesiastical Oath of 1791 - Tackett, Timothy, 1945- (Book collections on Project MUSE., 1986)
The imposition of a loyalty oath on French clergymen in the winter of 1790 was a turning point in the Revolutionary decade after 1789. What is more, there is a remarkable similarity between the geography of this oath--the regional percentages of those who accepted or rejected it--and the geographic patterns of religious practice and political behavior persisting into the twentieth century. Timothy Tackett investigates the origins and nature of this fascinating phenomenon. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.